Кинетические закономерности сополимеризации бутилметакрилата и фракции С9 - Бондалетов О. В. Олег Владимирович; Бондалетова Л. И. Людмила Ивановна; Бондалетов В. Г. Владимир Григорьевич; Таванова М. Э. (2011, 2011)
Заглавие с экрана